Comparison of 2D and 3D navigation techniques for percutaneous screw insertion into the scaphoid: Results of an experimental cadaver study - Catala-Lehnen, Philip; Nchtern, Jakob V.; Briem, Daniel; Klink, Thorsten; Rueger, Johannes M.; Lehmann, Wolfgang (Computer Aided Surgery, 2011)
Navigation in hand surgery is still in the process of development. Initial studies have demonstrated the feasibility of 2D and 3D navigation for the palmar approach in scaphoid fractures, but a comparison of the possibilities of 2D and 3D navigation for the dorsal approach is still lacking. The aim of the present work was to test navigation for the dorsal approach in the scaphoid using cadaver bones. After development of a special radiolucent resting splint for the dorsal approach, we performed 2D-and 3D-navigated scaphoid osteosynthesis in 12 fresh-frozen cadaver forearms using a headless compression screw (Synthes). The operation time, radiation time, number of trials for screw insertion, and screw positions were analyzed. In six 2D-navigated screw osteosyntheses, we found two false positions with an average radiation time of 5±2 seconds. Using 3D navigation, we detected one false position. A false position indicates divergence from the ideal line of the axis of the scaphoid but without penetration of the cortex. The initial scan clearly increased overall radiation time in the 3D-navigated group, and for both navigation procedures operating time was longer than in our clinical experience without navigation. Nonetheless, 2D and 3D navigation for non-dislocated scaphoid fractures is feasible, and navigation might reduce the risk of choosing an incorrect screw length, thereby possibly avoiding injury to the subtending cortex. The 3D navigation is more difficult to interpret than 2D fluoroscopic navigation but shows greater precision. Overall, navigation is costly, and the moderate advantages it offers for osteosynthesis of scaphoid fractures must be considered critically in comparisons with conventional operating techniques. © 2011 Informa UK Ltd.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Fracture fixation; Navigation; Osteosynthesis; Scaphoid; Screw insertion